Estrutura de habitat e tamanho da presa modulam a ecologia da predação de um pseudoescorpião social neotropical - Moura, Renan Fernandes (2017)
Predation strategies are driven by prey characteristics, such as nutritional value, or by habitat structure. Intrinsic factors such as living habits, behavioral plasticity and age-dependent nutritional requirements also shape predator ecology. Social living and behavioral interactions among nestmates favor more complex prey capture behaviors and group feeding dynamics. Here, we evaluated the feeding habits of the social pseudoscorpion Paratemnoides nidificator in two areas of Brazilian Cerrado savanna. These pseudoscorpions live under the bark of tree trunks that varies in size, depth and shape. Potentially, habitat structure could interfere with pseudoscorpion ambushing behavior and prey accessibility. We therefore assessed the hypotheses that: (i) larger colonies can capture larger and more variable prey sizes; (ii) habitat structure limits the size of captured prey; (iii) there is an age-dependent prey choice in which adult pseudoscorpions prefer larger prey. We evaluated prey items, colony composition and habitat structure of pseudoscorpions at two sites. Under laboratory conditions, we determined whether P. nidificator presents age-dependent feeding preferences by offering prey items of different sizes. Prey length and abundance varied between study sites and pseudoscorpion colonies were more numerous within a more urban. Additionally, larger colonies captured a wider variety of prey sizes. Colonies are able to capture large prey by using openings in tree bark as a trap; however, we observed this effect only in colonies situated under bark of intermediate width. Tree bark may play a role as a phenotype extension, providing conditions for or limitations to prey access and generating a heterogeneous benefit for colonies. In the laboratory, nymphs showed no preference for prey size, while adults mainly fed on larger ants. Small prey might represent an energetic complement for nymphs, reducing intraspecific competition and their exposure to larger, dangerous prey.